2008
DOI: 10.1152/ajpregu.90334.2008
|View full text |Cite
|
Sign up to set email alerts
|

Insulin acts at different CNS sites to decrease acute sucrose intake and sucrose self-administration in rats

Abstract: Figlewicz DP, Bennett JL, Aliakbari S, Zavosh A, Sipols AJ. Insulin acts at different CNS sites to decrease acute sucrose intake and sucrose self-administration in rats. Am J Physiol Regul Integr Comp Physiol 295: R388 -R394, 2008. First published June 4, 2008 doi:10.1152/ajpregu.90334.2008.-Findings from our laboratory and others have demonstrated that the hormone insulin has chronic effects within the CNS to regulate energy homeostasis and to decrease brain reward function. In this study, we compared the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
78
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(89 citation statements)
references
References 45 publications
(63 reference statements)
9
78
2
Order By: Relevance
“…At 24 h after injection, the VTA GLP-1R activation still potently (Ͼ50%) reduced chow intake and body weight gain at both doses tested, whereas NAc shell injection produced a small effect only on chow intake at the highest dose tested, potentially indicating differential sensitivity of those two sites to anorexic effects of GLP-1 stimulation. These results contrast with those obtained for insulin, in which a reduction in free-feeding and food-motivated behavior was modulated by a disparate receptor population (Figlewicz et al, 2008). Thus, the mesolimbic GLP-1Rs can contribute to both free-feeding and motivated behavior for palatable food.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…At 24 h after injection, the VTA GLP-1R activation still potently (Ͼ50%) reduced chow intake and body weight gain at both doses tested, whereas NAc shell injection produced a small effect only on chow intake at the highest dose tested, potentially indicating differential sensitivity of those two sites to anorexic effects of GLP-1 stimulation. These results contrast with those obtained for insulin, in which a reduction in free-feeding and food-motivated behavior was modulated by a disparate receptor population (Figlewicz et al, 2008). Thus, the mesolimbic GLP-1Rs can contribute to both free-feeding and motivated behavior for palatable food.…”
Section: Discussioncontrasting
confidence: 89%
“…Several brain areas provide likely targets for the effects of EX4 and include brainstem and hypothalamic GLP-1R-expressing nuclei previously shown to play a role in GLP-1 anorexia (Schick et al, 2003;Hayes et al, 2009) that project to the mesolimbic system (e.g., VTA). In fact, for another peripheral hormone, insulin, despite the presence of insulin receptors in the VTA, only the hypothalamic stimulation was effective in reducing food reward (Figlewicz et al, 2008). However, our data showing a suppression of operant responding with a direct VTA or NAc EX4 microinjection demonstrate a direct impact of EX4 on these mesolimbic areas.…”
Section: Discussioncontrasting
confidence: 53%
“…This effect was primarily caused by a drop in the consumption of carbohydrates. This finding ties in with experiments in rats indicating that insulin administration to the CNS reduces sugar intake (Figlewicz et al, 2008) and suggests that, in accordance with the major role of peripheral insulin for blood glucose regulation, the anorexigenic effect of the hormone on the brain might focus on carbohydrates. However, the relative paucity of available data in humans (Benedict et al, 2008;Hallschmid et al, 2012;Jauch-Chara et al, 2012) and animals (Woods et al, 1979;McGowan et al, 1992;Air et al, 2002;Clegg et al, 2003Clegg et al, , 2006 at the moment does not permit sound conclusions on macronutrient-specific effects of brain insulin on eating behavior (for review see Kullmann et al, 2016;Lee et al, 2016).…”
Section: Discussionsupporting
confidence: 72%
“…However, it is in the same range as the dose required for a feeding response to third ventricular insulin. We also note that Figlewicz and colleagues (15) likewise found that a dose of 5 mU insulin directly into the ventral tegmental area was ineffective in reducing food intake. There could be a number of explanations for the need for such high doses for the anorectic behavioral response compared with the lower doses that induce an acute short-lived signaling response.…”
Section: Discussionmentioning
confidence: 49%
“…On the day of testing, 3 h prior to lights off, the food cups were removed from the cages, and the rats were injected with vehicle (saline) or insulin into the amygdala (Humulin R; Eli Lilly, Indianapolis IN). The doses of insulin used in our experiments were selected based on previous experiments taken from the literature for intracerebroventricular or intraneuropil administrations (15,16,40,46). Solutions were prepared fresh before injection.…”
Section: General Conditions To the Experimentsmentioning
confidence: 99%